Monthly administrations of milbemycin oxime plus afoxolaner chewable tablets to prevent Angiostrongylus vasorum infection in dogs - Lebon, Wilfried (Parasit Vectors, 2016)
BACKGROUND: Infection of dogs with the cardiopulmonary nematode Angiostrongylus vasorum may result in severe clinical disease therefore adequate prevention is necessary. A randomized, negative control, blinded study was conducted to evaluate the efficacy in the prevention of canine A. vasorum infection after monthly administrations of NexGard Spectra®, a novel chewable tablet formulation combining the insecticide and acaricide afoxolaner and the anthelmintic milbemycin oxime, in a multiple challenge (trickle infection) model. METHODS: Twenty beagle dogs were challenged orally with doses of approximately 32–43 third-stage larvae of A. vasorum once every other week on seven occasions (Study Days -7, 7, 21, 35, 49, 63 and 77). Ten dogs were administered NexGard Spectra® as close as possible to the minimum recommended dose of afoxolaner and milbemycin oxime, i.e. 2.5 mg/kg body weight and 0.5 mg/kg body weight, respectively, four times at monthly intervals (Study Days 0, 28, 56 and 84) while the remaining ten dogs served as untreated controls. For parasite recovery and count, dogs were euthanized humanely and necropsied six to eight days following the last treatment (Study Days 90–92). Beginning six weeks after first inoculation, faeces were collected on a bi-weekly basis and examined for first-stage larvae of A. vasorum. RESULTS: Untreated dogs harboured 39–95 adult A. vasorum (geometric mean, 66.4), while zero to 24 adult A. vasorum were recovered from the treated dogs (geometric mean, 3.4; P < 0.0001). Thus, efficacy of NexGard Spectra® administered at monthly intervals against incoming A. vasorum was 94.9 %. Compared to the untreated controls, larval excretion of the treated dogs was reduced by 99.9 % (P < 0.0001). CONCLUSION: Results of this study demonstrate that NexGard Spectra®, when administered at monthly intervals, can effectively prevent canine A. vasorum infection.